Attribute-based bilateral access control scheme for cloud storage - LI Qi; FAN Haoyuan; CHEN Wei; XIONG Jinbo; HAN Lidong; LI Rui (Tongxin xuebao)
In the existing cloud storage systems, the fine grained and bilateral access control schemes suffer from weak security model and unverifiable outsourced decryption result. To address this problem, an attribute-based bilateral access control scheme for cloud storage was proposed. Firstly, the formal definition and secure model of adaptively secure and verifiable outsourced bilateral CP-ABE was given. Secondly, combining with the batch verification technology, the attribute based bilateral access control scheme was constructed on the composite order groups, which enabled both the data owner and data user to simultaneously define the access policies for each other. Finally, the security analysis showed that the proposed scheme was indistinguishable and existential unforgeable under adaptive security models against chosen plaintext attacks and chosen message attacks, respectively. The experimental results show that the proposed scheme achieves high performance on the user side, where the computational overhead of matching, decryption, and verification is reduced.